2016
DOI: 10.1016/j.jcp.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

SAMBA: Sparse Approximation of Moment-Based Arbitrary Polynomial Chaos

Abstract: Please cite this article in press as: R. Ahlfeld et al., SAMBA: Sparse approximation of moment-based arbitrary polynomial chaos, J. Comput. Phys. (2016), http://dx.doi.org/10.1016/j. jcp.2016.05.014 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 35 publications
0
81
0
Order By: Relevance
“…Existing studies [25,37,38] have reported that the SGNI is suitable for uncertainty analysis due to its good performance, especially in estimating the low order moments of the system response. However, most researchers are using the SGNI with the traditional univariate integration points, such as the Gauss-Hermite or Gauss-Legendre integration nodes.…”
Section: The Proposed Methods For Up Analysismentioning
confidence: 99%
“…Existing studies [25,37,38] have reported that the SGNI is suitable for uncertainty analysis due to its good performance, especially in estimating the low order moments of the system response. However, most researchers are using the SGNI with the traditional univariate integration points, such as the Gauss-Hermite or Gauss-Legendre integration nodes.…”
Section: The Proposed Methods For Up Analysismentioning
confidence: 99%
“…Here, only the the main relations are summarised. Full details are described in Ahlfeld [17]. The Hankel matrix of the moments is formed by…”
Section: A Optimal Gaussian Quadrature Rules For Arbitrary Random Vamentioning
confidence: 99%
“…Non-intrusive polynomial chaos methods can be applied to propagate any probability distribution or random data set, as long as they have finite moments and their moment matrix is determinate in the Hamburger sense [17]. To circumvent the fact that heavy-tailed distributions have infinite moments, the distributions need to be truncated [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, being nested by definition, they allow for the efficient construction of sparse grids, thus enabling high-dimensional UQ studies. We note that this paper focuses on continuous PDFs of arbitrary shapes and does not consider data-driven approaches which define a PDF through its moments without any further assumptions about it [31,32].Due to a number of desirable properties, e.g., granularity, interpolation, and quadrature stability, and nestedness, weighted Leja nodes have been getting increasing attention in the context of approximation and UQ [16,30,[33][34][35][36]. Nonetheless, with the exceptions of [34,37,38] where beta distributions are considered for the parameters, the use of Leja nodes has been limited to uniform and log-normal parameter distributions.…”
mentioning
confidence: 99%